Sintesis Biopelumas Dari Minyak Biji Jarak: Pengaruh Kecepatan Pengadukan Dan Suhu Reaksi - Nico Gunawan; Irdoni Irdoni; Nirwana Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Lubricants is an inseparable part of machine. Lubricants used to protect engine components from worn-out. Along with the increasing demands on materials that are environmentallyfriendly and renewable, vegetable oils or animal fats based biolubricants can be claimed as a solution. Jatropha curcas oil is an oil that can not be consumed cause had phorbol ester andkurkin that are toxicthus potentially used as raw material for biolubricants. This research purposes to study the synthesis of biolubricants from castor oil to observe the effect of stirring speed and esterification reaction temperature. The research was begun with the saponification of jatropha curcas oil to make fatty acid. Furthermore, fatty acids will be esterified with etylen glycol ona mole ratio of 1: 4, and time reaction for 4 hours, stirringspeed 150, 180, 210 rpm, and the reaction temperature of 120oC, 150oC, and 180oC. The yield raised with the increase of stirring speed and reaction temperature. Temperature influence is more significant than the speed of stirring. The highest yield is 91,96% at reaction temperature at 180 C and a stirring speed of 180 rpm with a flash point 435°C, pour point 4°C, density 0,9005 g/ml and viscosity index amounted 161,678.Keywords: biolubricants, esterification, etylen glycol, jatropha curcas oil, yield